Assessment of polycyclic aromatic hydrocarbons in indoor and outdoor air of preschool environments (3–5 years old children) - Oliveira, Marta (2016)
This work characterizes levels of polycyclic aromatic hydrocarbons (PAHs) in indoor and outdoor air of preschool environments, and assesses the respective risks for 3–5-years old children. Eighteen gaseous and particulate (PM1 and PM2.5) PAHs were collected indoors and outdoors during 63 days at preschools in Portugal. Gaseous PAHs accounted for 94–98% of total concentration (ΣPAHs). PAHs with 5–6 rings were predominantly found in PM1 (54–74% particulate ΣPAHs). Lighter PAHs originated mainly from indoor sources whereas congeners with 4–6 rings resulted mostly from outdoor emissions penetration (motor vehicle, fuel burning). Total cancer risks of children were negligible according to USEPA, but exceeded (8–13 times) WHO health-based guideline. Carcinogenic risks due to indoor exposure were higher than for outdoors (4–18 times).